Pembenihan Ikan Baung (Hemibagrus nemurus) pada Kelompok Perikanan Sawah Mandiri - Sukendi Sukendi; Thamrin Thamrin; Ridwan Manda Putra; Nuraini Nuraini; Ade Yulindra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The purpose of community service activities carried out is to provide knowledge and technology about Hemibagrus nemurus fish hatchery technology through artificial spawning at the Independent Sawah Fishery Group in Sawah Village, North Kampar District, Kampar Regency. The method applied in this community service activity is the lecture method, discussion and field practice. The lecture method was carried out in the meeting room of the Chairperson of the Independent Sawah Fishery Group, Sawah Village, North Kampar District, Kampar Regency by providing material about the hatchery of H. nemurus fish through artificial spawning. The results of the evaluation of changes in knowledge carried out on 11 participants of the activity showed that 8 people (72.73%) had been able to absorb the material given with a very good predicate, 2 people (18.18%) could absorb the material given with a good predicate, 1 people (9.09%) could absorb the material with sufficient predicate, while those who received less predicate and less predicate were not found. The results of the skills evaluation show that members of the Independent Sawah Fishery Group have been able to directly practice the activities that have been given in the field regarding H. nemurus fish hatchery technology. Meanwhile, the results of the impact evaluation show that members of the Sawah Mandiri Fishery Group have started to hatch H. nemurus fish in addition to the catfish hatchery that has been done so far.